2019
DOI: 10.1111/jopr.13109
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Additive Manufactured Indices Performed from a Virtual Diagnostic Waxing for Direct Composite Diastema Closure Combined with Resin Infiltration Technique on White Spot Lesions: A Case Report

Abstract: The present article describes the resin infiltration technique to address white spots lesions presented on anterior and premolar teeth of a young patient after orthodontic treatment and the digital workflow for planning a diastema closure on the maxillary anterior teeth using facial photographs, an intraoral scanner, a facially driven diagnostic waxing using a dental computer‐aided design (CAD) software, and 3‐piece additive manufactured (AM) clear silicone indices. The virtual design of the silicone indices w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…Recently, studies have proposed the use of 3D printed "silicone indices" and have shown that the digital design and the resin material provide higher control of index thickness and border of the index. 22,23 Similarly, the results of this study also showed that the thermoplastic guide improved the accuracy of veneer preparation by 0.11−0.09 mm and provided more consistent preparation than the silicone guides. The mechanical properties of the resin material are advantageous; 5 thus, stronger guides can be much thinner to manage the preparation depth in a more controlled and precise manner.…”
Section: Discussionsupporting
confidence: 66%
“…Recently, studies have proposed the use of 3D printed "silicone indices" and have shown that the digital design and the resin material provide higher control of index thickness and border of the index. 22,23 Similarly, the results of this study also showed that the thermoplastic guide improved the accuracy of veneer preparation by 0.11−0.09 mm and provided more consistent preparation than the silicone guides. The mechanical properties of the resin material are advantageous; 5 thus, stronger guides can be much thinner to manage the preparation depth in a more controlled and precise manner.…”
Section: Discussionsupporting
confidence: 66%
“…In this field, scanners with integrated caries detection systems based on noninvasive optical systems, described in Section 3.5, are already under development and are spreading on the market. The first scanner with integrated caries detection technology was TRIOS 4, which integrates fluorescence technology, whose diagnostic reliability was investigated in many of the articles analyzed [48][49][50]. Even near-infrared lights have the ability to locate carious lesions, and this technology has been implemented in iTero Element 5D.…”
Section: Discussionmentioning
confidence: 99%
“…Davidovich et al [47,48] presented an innovative therapeutic approach for endodontically treated teeth and treatment for the hypomineralization of molar incisors (MIH) in children using a digital workflow with an IOS and CAD/CAM for restoration, addressing the uncooperative behavior of children and enabling the preservation of the tooth structure and long-lasting restoration. Revilla-Leon et al [49,50] and Park et al [51] instead presented a digital workflow for esthetic rehabilitation (e.g., in case of diastema) using a combination of facial and intraoral scanners and additive manufactured (AM) clear silicone indices. DuVall [52] used an intraoral scanner and milling unit to fabricate a CAD/CAM radiographic and surgical guide for use with a Cone Beam Computed Tomography system.…”
Section: Oral Conditions Diagnosed Using An Iosmentioning
confidence: 99%
“…A deviation of 0.140 mm was consistently detected in the thickness of the trial restoration, and the deformation of the silicone matrix caused a deviation in the trial restoration [29], further affecting the accuracy of the measurement points [30]. Some studies have also reported the deviation of trial restorations made from a silicone matrix and proposed a 3D-printed index to improve accuracy [31][32][33].…”
Section: Discussionmentioning
confidence: 99%